2021
DOI: 10.3390/agronomy11030561
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive and Surface Characterization of Mediterranean Agrifood Processing Wastes: Prospection for Pesticide Removal

Abstract: The sustainable management of biomass is a key global challenge that demands compliance with fundamental requirements of social and environmental responsibility and economic effectiveness. Strategies for the valorization of waste biomass from agrifood industries must be in line with sustainable technological management and eco-industrial approaches. The efficient bioremoval of the pesticides imazalil and thiabendazole from aqueous effluents using waste biomass from typically Mediterranean agrifood industries (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…is explains why water sorption isotherms are useful thermodynamic tools for predicting the interaction between water and food components. Moreover, sorption isotherms can be used to explore the structural features of cherry powders, such as specific surface area, pore volume, pore size distribution, and crystallinity [8][9][10]. Such data are key elements for optimizing storage conditions and packaging, and they can be used in the food industry to improve the aroma retention, color, texture, nutrients [11], and biological stability of food products [12].…”
Section: Introductionmentioning
confidence: 99%
“…is explains why water sorption isotherms are useful thermodynamic tools for predicting the interaction between water and food components. Moreover, sorption isotherms can be used to explore the structural features of cherry powders, such as specific surface area, pore volume, pore size distribution, and crystallinity [8][9][10]. Such data are key elements for optimizing storage conditions and packaging, and they can be used in the food industry to improve the aroma retention, color, texture, nutrients [11], and biological stability of food products [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fernandez-Lopez et al. (2021) have characterized the physicochemical properties of the globe artichoke canning industry waste.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Amoah et al (2020) have demonstrated that bread formulated with flour from plant-based byproducts, such as the globe artichoke leaves and stems, presents increased fibers and bioactive compound contents. Fernandez-Lopez et al (2021) have characterized the physicochemical properties of the globe artichoke canning industry waste. Such a research has been addressed to obtain new data on the relationship between adsorptive parameters and bioremoval capacity of the artichoke waste, and to reduce water pollutants through the reuse and recycling of lignocellulosic residues.…”
Section: Discussionmentioning
confidence: 99%
“…Biomass can be broadly defined as any organic material derived from renewable biological sources [ 37 ]. Waste biomass possesses irregular surfaces, varying pore sizes, and active functional groups and is abundant in nature [ 38 ]. Converting waste, such as biomass, into materials suitable for environmental applications is a green and eco-friendly waste management approach.…”
Section: Introductionmentioning
confidence: 99%